MODEL PENDAMPINGAN DALAM MEWUJUDKAN JIWA KEWIRAUSAHAAN BAGI ANAK JALANAN DI KOTA PALEMBANG - Dedi Rianto Rahadi (Universitas Paramadina, 2014)
AbstractEntrepreneurial spirit can have the character of street children through education, hard work and comprehensive knowledge. The general objective of the research is to produce a model entrepreneur community among street children and realize the nature and behavior of self to not be a burden to others. The study design was a multiple case study. Methods of data collection using a combination of approaches (triangulat which include: surveys, observation, field study, FGD (focus group discussion), PRA (Participatory rural appraisals) and action research. Samples numbered 33 street children in the city of Palembang, results showed some children street in the city of Palembang born of the economic downturn the bottom layer of society. they become street children due to the low socio-economic conditions of the family and his efforts to use the money to support their families and personal needs such as playing online games at Internet cafes. Activities undertaken by street children is singing on the bus, begging, hawkers (selling newspapers, food and soft drinks). Conclusions Entrepreneur modeling studies can be done through family empowerment approaches and models of mentoring, especially in terms of economy, education and religion. Through family involvement can accelerate the growth of the entrepreneurial spirit for street children